2001
DOI: 10.1021/jp0040345
|View full text |Cite
|
Sign up to set email alerts
|

N2O Adsorption and Photochemistry on High Area TiO2 Powder

Abstract: The adsorption and photochemistry of N 2 O chemisorbed on TiO 2 powder has been investigated. At 157 K, nitrous oxide is molecularly adsorbed on the reduced titanium dioxide. Adsorption on the TiO 2 surface takes place through both the N and O ends of the nitrous oxide molecule. The photochemistry of the adsorbed N 2 O molecules was studied at 157 K by use of UV irradiation in the range 2.1-5.0 eV. The photoactivity of the adsorbed molecule is dependent on the N 2 O coverage. At low coverages, the adsorbed N 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 34 publications
5
49
0
1
Order By: Relevance
“…In another example, Rusu and Yates. [705] showed that photocatalytic conversion of N 2 O was slightly faster if the N-end of the molecule was bound to surface Ti 4+ sites rather than if the O-end was utilized. Also, N 2 (the preferred product) was formed at low N 2 O coverages with the N-end down species.…”
Section: Structure Sensitivitymentioning
confidence: 99%
See 3 more Smart Citations
“…In another example, Rusu and Yates. [705] showed that photocatalytic conversion of N 2 O was slightly faster if the N-end of the molecule was bound to surface Ti 4+ sites rather than if the O-end was utilized. Also, N 2 (the preferred product) was formed at low N 2 O coverages with the N-end down species.…”
Section: Structure Sensitivitymentioning
confidence: 99%
“…Surface coverage has been shown to affect photocatalytic activity on TiO 2 surfaces in several examples [541,705,[717][718][719]. This author and coworkers [541] have shown that the rate of trimethyl acetate (TMA) photodecomposition on R TiO 2 (110) depended on the TMA surface coverage.…”
Section: Coverage Dependencementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, photocatalysis emerged as a new scientific area when Fujishima and Honda carried out photolysis of water into environmentally clean fuels (hydrogen and oxygen) using a titanium dioxide electrode in an electrochemical cell [1]. Ever since, heterogeneous photocatalysis by means of TiO 2 has been widely accepted and exploited as an efficient technology for killing bacteria and degrading organic and inorganic pollutants [2][3][4][5][6][7][8][9][10][11][12][13]. Moreover, titanium dioxide (TiO 2 ) has been regarded as an excellent semiconductor photocatalyst because of its performance, low cost, nontoxicity, stability, and availability.…”
Section: Introductionmentioning
confidence: 99%